The Legal Protection against Accountability for Criminal Acts of Narcotics Abuse in Indonesia - Novalina, Novalina; Hayatuddin, Khalisah; Salia, Erli; Yusuf, Hambali; Is, Muhamad Sadi (Universitas Islam Sultan Agung, 2024)
Narcotics crimes are increasing from year to year in both quantity and quality in Indonesia. The narcotics law emphasized that the legal position of narcotics abusers was no longer seen as perpetrators but rather as victims, there was a change in the legal paradigm in legal protection for narcotics abusers. As a victim, the perpetrator must receive legal protection. Legal protection for narcotics abusers was implemented in the form of medical rehabilitation and social rehabilitation which were discretionary from the types of punishment as regulated in Article 10 of the Criminal Code. The problem was how to protect the law against criminal liability for narcotics abusers and how to optimize legal protection for narcotics abusers. Normative research was used as the method in this research, and the secondary data obtained from reviewing related laws and regulations and relevant literature. The result explained that legal protection for the criminal liability of narcotics abusers was determined through a judge's decision by placing narcotics abusers in rehabilitation institutions. Then, optimizing legal protection for narcotics abusers was carried out by equalizing the perceptions of all law enforcement officials regarding the need for legal protection for crime victims as well as unifying views and providing a deep understanding of the aims and objectives of providing rehabilitation.